Improving the modularity of web-application models with aspects. (2015) - Zhang, Gefei; Hölzl, Matthias
Modern web applications often contain features, such as landmarks, access control, adaptation, or rich UI, that are difficult to model modularly with existing model-driven web engineering (MDWE) approaches. We show how HiLA, an aspect-oriented extension for UML state machines, can represent these features as aspects. HiLA models achieve a high grade of separation of concerns and satisfy the 'Don't Repeat Yourself' (DRY) guideline. Particularly, interesting features of HiLA are: 1) its capability to serve as a substrate for domain-specific modelling languages; 2) declarative combination of features to precisely control the desired overall behaviour of an application and ensure that different features do not interfere with each other; 3) support for automatic and formal verification of (existence or absence of) interference between features. HiLA can be used on top of a number of state-machine-based MDWE approaches to enhance the modularity of models.